Implementasi Sistem Lost and Found Kampus Berbasis Web Terintegrasi Geolocation dan Evaluasi MOS - Zickrian, Firdaus Khotibul; Kurnia, Maulida Cahya; Devyana, Amanda; Apriyanto, Andika; Ramadhani, Ryandika Syauqi; Pramita, Cinantya (STMIK Banjarbaru, 2026)
This study developed a web-based Lost and Found system to address the issue of reporting lost items on campus, which was previously done through informal and decentralized media. The system was designed using a User-Centered Design approach and equipped with features for reporting, searching, category filtering, photo uploading, and geolocation-based location tagging. Evaluation was conducted through black box testing and user acceptance testing using Mean Opinion Score (MOS). The test results showed that all functions worked according to specifications, while the average MOS value of 4.98 indicated a very good level of user acceptance. These findings confirm that the developed system is capable of improving the effectiveness of the item retrieval process and is suitable for use as a service to support academic activities.Keywords: Lost and found; Geolocation; User-centered design; Mean opinion score; Information systemAbstrakPenelitian ini mengembangkan sistem Lost and Found berbasis web untuk mengatasi permasalahan pelaporan barang hilang di kampus yang sebelumnya dilakukan melalui media informal dan tidak terpusat. Sistem dirancang menggunakan pendekatan User-Centered Design dan dilengkapi fitur pelaporan, pencarian, filter kategori, unggah foto, serta penandaan lokasi berbasis geolocation. Evaluasi dilakukan melalui pengujian black box dan pengujian penerimaan pengguna menggunakan Mean Opinion Score (MOS). Hasil pengujian menunjukkan seluruh fungsi berjalan sesuai spesifikasi, sedangkan nilai MOS rata-rata sebesar 4,98 mengindikasikan tingkat penerimaan pengguna yang sangat baik. Temuan ini menegaskan bahwa sistem yang dikembangkan mampu meningkatkan efektivitas proses temu-kembali barang dan layak digunakan sebagai layanan pendukung aktivitas sivitas akademika.